Junie B. Jones and the mushy gushy valentime [i.e. valentine] - Park, Barbara; Brunkus, Denise (New York : Random House, 1999)
When Junie B. Jones receives a mushy gushy "valentime" on Valentine's Day, she tries to find out who in her kindergarten class is her secret admirer.
"A Stepping Stone book."
Keywords: Valentine's Day -- Fiction; Valentines -- Fiction; Kindergarten -- Fiction; Schools -- Fiction